Building gen z work character through the among learning system in vocational education - Mariah, Siti; Soeparwati, Soeparwati; Hesline Palandi, Esther (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study explores the development of Generation Z’s work character through the implementation of the Among Learning System in vocational education. Employing a qualitative research methodology based on library research and literature review, the study critically examines existing theories and practices related to character building, generational characteristics, and innovative learning models within vocational contexts. The Among Learning System, rooted in cultural and communal learning traditions, emphasizes holistic personal development, including ethics, discipline, responsibility, and collaboration—key attributes for preparing Gen Z students for the dynamic world of work. The analysis reveals that integrating culturally grounded learning methods like the Among Learning System effectively nurtures essential work ethics and soft skills among vocational students. This system fosters not only technical competence but also interpersonal and intrapersonal skills that are critical for employability and professional success. Findings from the literature highlight the challenges Gen Z faces in adapting to workplace demands, such as digital distractions, preference for instant gratification, and diverse learning needs. The Among Learning System addresses these challenges by promoting self-regulation, communal responsibility, and reflective practices within the learning environment. This study contributes to vocational education by offering a framework for educators and policymakers to incorporate culturally relevant pedagogies that align with Gen Z’s unique characteristics. It also underscores the importance of character education alongside technical skills development in vocational training to produce well-rounded, resilient graduates ready to meet future workforce challenges. Further empirical research is recommended to validate these theoretical findings and explore the practical implementation of the Among Learning System across diverse vocational settings.